Evaluating the Perspectives of the Faculty of Dentistry Students on Pediatric Dentistry: A Survey Study - Yıldız, Şemsettin (Cumhuriyet University Faculty of Dentistry, 2022)
Objectives: This study aims to evaluate the approach of the students of the faculty of dentistry who look after children in their internships to pediatric dentistry, which includes preventive dentistry. Materials and Methods: A questionnaire consisting of 20 questions was prepared. The questionnaire was administered to the students online in a stress-free environment away from the exam environment. The data were coded and analyzed in a computer environment. Categorical divisions are expressed as numbers and percentages. The chi-square test was used to compare the evaluations of the participants according to their ancestry and class. Results: 55.9% of the participants said they liked caring for pediatric patients. While 72.8% of them stated they were nervous when their child looked After graduation, 67.6% answered that they could think of treating pediatric patients routinely in their professional life. However, not very often, while 25% of them said yes, and 7.4% of them did not think unless it was necessary. Although women are more anxious when a child is sick, they prefer to look after a child more than men (p<0.05). There was no significant difference according to the class of the participants in choosing to treat the child or adult patient (p>0.05). There is no statistically significant difference in the participants' evaluations regarding the institutions that they think provide the best pediatric dentistry service according to class and gender (p>0.05). Dentistry faculties were the most frequent response for both classes and genders. Conclusions: Despite the large population of children and young people in our country, it has been observed that future dentist candidates are not willing enough for these treatments. Increasing their knowledge and experience in treating pediatric patients during their education will help more pediatric patients be treated © This work is licensed under Creative Commons Attribution 4.0 International License
Diş Hekimliği Fakültesi Öğrencilerinin Çocuk Diş Hekimliğine Bakış Açısını Değerlendirmek: Anket Çalışması
Keywords: Dentistry students; Pedodontics; Preventive dentistry